2015
DOI: 10.3390/foods4020240
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Seaweed and Seaweed-Containing Foods in the UK: Focus on Labeling, Iodine Content, Toxicity and Nutrition

Abstract: Seaweed (edible algae) is not a staple food in the Western diet, despite occasional use as a traditional ingredient in coastal areas. High nutritional value, combined with the expansion of the health-food industry, has led to a resurgence of seaweed in the British diet. While seaweed could be useful in tackling dietary iodine insufficiency, consumption of some species and sources of seaweed has also been associated with risks, such as toxicity from high iodine levels, or accumulation of arsenic, heavy metals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 33 publications
2
104
0
2
Order By: Relevance
“…Retails samples of kelp ( n = 20; species unknown) from the United Kingdom had a wide range of I concentrations from 25 to 1,200 mg/kg dw, with variations seen among different samples of the same product (Norman, Pickford, Sanders, & Waller, ). However, in a later study, Bouga and Combet () indicated that a limited amount of the sampled U.K. seaweed‐containing products (10%; n = 224) provided information on I. Given estimated calculations for I exposure per serving (ranging from 0.5 g to 350 g), 26 seaweed products could potentially lead to I above the EU UL of 0.6 mg/day (Bouga & Combet, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retails samples of kelp ( n = 20; species unknown) from the United Kingdom had a wide range of I concentrations from 25 to 1,200 mg/kg dw, with variations seen among different samples of the same product (Norman, Pickford, Sanders, & Waller, ). However, in a later study, Bouga and Combet () indicated that a limited amount of the sampled U.K. seaweed‐containing products (10%; n = 224) provided information on I. Given estimated calculations for I exposure per serving (ranging from 0.5 g to 350 g), 26 seaweed products could potentially lead to I above the EU UL of 0.6 mg/day (Bouga & Combet, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a later study, Bouga and Combet () indicated that a limited amount of the sampled U.K. seaweed‐containing products (10%; n = 224) provided information on I. Given estimated calculations for I exposure per serving (ranging from 0.5 g to 350 g), 26 seaweed products could potentially lead to I above the EU UL of 0.6 mg/day (Bouga & Combet, ). The lack of information on seaweed type, source, and I content means that estimates on the safety and suitability of such products still need to be refined, also considering the population exposed.…”
Section: Resultsmentioning
confidence: 99%
“…Major food constituents with side-effects are iodine, fibers, and sodium (in seasoned laver). Iodine has beneficial effects on thyroid gland functioning, but excessive intake should be avoided to prevent potential adverse effects such as autoimmune thyroiditis or hypothyroidism [94][95][96][97][98]. Overconsumption of fibers can lead to vomiting or abdominal pain with diarrhea in people with sensitive stomachs and may cause dyspepsia even in healthy people due to generation of gases in the digestive system [99].…”
Section: Control Of Chemical Risksmentioning
confidence: 99%
“…The main limitations affecting the application of algae in food products are related to sensory (residual flavor and aroma) and toxicological aspects (high iodine levels, or accumulation of arsenic, heavy metals, and contaminants) (Bouga & Combet, 2015). These risks must be minimized in order to maximize the technological, functional, and nutritional advantages that are associated with macro-and microalgae materials and bioactive compounds.…”
Section: Antimicrobial Potential Of Algae Validated In Real Food Matrmentioning
confidence: 99%